Mineral admixtures in cement and concrete - Bapat, Jayant D. (Boca Raton, Fl. : CRC Press, 2013)
'Written for structural engineers, this book explains how micro-structurally engineered concrete can substantially enhance the durability and service life of concrete structures. The text addresses the sustainable development of cement and the construction industry and provides an understanding of the materials aspects of mineral admixtures and their positive impact on the hydration and durability of concrete in an effort to encourage greater utilization of other wastes in cement and concrete. The author explains the development of strength-giving chemical phases during hydration and the refinement of pore structure of concrete and consequent improvement in the strength and durability of concrete'--
Includes bibliographical references and index.
Keywords: Cement -- Additives; Concrete -- Additives